1992
DOI: 10.1200/jco.1992.10.2.219
|View full text |Cite
|
Sign up to set email alerts
|

MACOP-B treatment in diffuse large-cell lymphoma: identification of prognostic groups in an Italian multicenter study.

Abstract: These results confirm the effectiveness of MACOP-B in advanced-stage DLCL at low or intermediate risk; however, high-risk patients are in urgent need of new therapeutic approaches. A better definition of prognostic features would allow a more reliable comparison of different treatment regimens, as well as an effective tailoring of therapy by prognostic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
2
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 15 publications
1
18
2
1
Order By: Relevance
“…Some studies [3][4][5][6][7][8][9] (although not all studies 1,15 ) have reported that bulky disease is an adverse prognostic factor in patients with aggressive lymphomas. Surgery may play a role in the management of such patients by removing malignant cells that are resistant to chemotherapy and radiotherapy and that eventually may give rise to distant metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies [3][4][5][6][7][8][9] (although not all studies 1,15 ) have reported that bulky disease is an adverse prognostic factor in patients with aggressive lymphomas. Surgery may play a role in the management of such patients by removing malignant cells that are resistant to chemotherapy and radiotherapy and that eventually may give rise to distant metastases.…”
Section: Discussionmentioning
confidence: 99%
“…1 The IPI includes independent prognostic features, such as age and serum lactate dehydrogenase (LDH) level. A number of groups have suggested that T-cell phenotype, 2 bulky disease, [3][4][5][6][7][8][9] and total radiotherapy dose 10 also are important prognostically.…”
mentioning
confidence: 99%
“…BM involvement has also been reported as an adverse prognostic feature in DLCL, especially if associated with intermediate/high IPI scores. [51][52][53] In our series, 23 out of 35 patients with BM involvement are now in continuous CR and it is quite likely that, here too, rituximab played a major role in this particular setting. Finally, a favorable outcome was also obtained in the subgroup of patients with DLB-CL and ABC phenotype, a phenotypic subgroup characterized by a reduced response to both conventional and intensified approaches.…”
Section: Tablementioning
confidence: 98%
“…Specific sites of tumour involvement, especially the bone marrow, but also other sites such as the gastrointestinal tract, have been identified as significant adverse prognostic factors. 26 Some extranodal sites, such as brain 27 or testis, 28 require special treatment strategies, and DLBCL which have arisen in those sites constitute particularly aggressive malignancies (see the section 'Aggressiveness indicators', below). Response rate after primary treatment is highly predictive of outcome.…”
Section: Tumour-related Variablesmentioning
confidence: 99%